Redirection theory and antisocial travel behavior: Configural antecedents to nascent road-road signaling - Herbst, L.; Reinartz, D.; Woodside, Arch (2017)
© 2017 by Emerald Publishing Limited. The focus of this study is on analyzing influencing factors of antisocial travel-related behaviors - in particular road rage. Building on the concept of redirection, the current chapter develops a theory of natural and planned redirection to derive starting points for demarketing antisocial behaviors. A fuzzy set qualitative comparative analysis (fsQCA) with survey data from 6,811 consumers from the DDB Life Style Study is used to gain insights into the individuals behind road rage. Results show that specific kinds of anti- and prosocial behavior associate with high and low levels of road rage, respectively. The study finds that these prosocial behaviors may function as natural redirection mechanisms and prevent or reduce road rage. Thereby, the findings extend previous analyses of road rage and allow for deriving theoretical and policy implications.